PENGARUH E-BANKING DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERBANKAN DI INDONESIA - Wisnu Handoyo Murti (LPMP Imperium, 2019)
This study aims to examine the effect of e-banking and the implication of good corpoarte governance on banks performance. The rapid movement of digital technology in dealing with transaction provides both challange and opportunities. Banks, should understand the digital trend to survive in digital era, while the good corporate governance practice will impact banks performance through planning strategies and decision making. This paper use panel regression to analyze the data, and banks that listed in Indonesia Stock Exchange is used as sample. The result indicates that e-banking, board size, and institutional ownership do not statistically significant in influencing banks performance. While ownership concentration and independent commissioner has positive effect on banks performance.